Plague history: Yersin's discovery of the causative bacterium in 1894 enabled, in the subsequent century, scientific progress in understanding the disease and the development of treatments and vaccines. (March 2014) - Butler, T.
Abstract The causative bacterium of plague was described and cultured by Alexandre Yersin in Hong Kong in 1894, after which transmission of bacteria from rodents by flea bites was discovered by Jean‐Paul Simond in 1898. Effective treatment with antiserum was initiated in 1896, but this therapy was supplanted by sulphonamides in the 1930s and by streptomycin starting in 1947. India suffered an estimated 6 million deaths in 1900–1909, and Vietnam, during its war in 1965–1975, accounted for approximately 80% of the world's cases; since then, African countries have dominated, with >90% of the world's cases in the 1990s and early 21st century. Serological diagnosis with fraction 1 antigen to detect anti‐plague antibodies was developed in the 1950s. Vaccine development started in 1897 with killed whole bacterial cells, and this was followed by a live attenuated bacterial vaccine, leading to millions of persons receiving injections, but the benefits of these vaccines remain clouded by controversy. Plasmid‐mediated virulence was established in 1981, and this was followed by specific DNA methods that have allowed detection of plague genes in skeletal specimens from European graves of the sixth to 17th centuries.